Polycaprolactone-gelatin membrane as a sealant biomaterial efficiently prevents postoperative anastomotic leakage with promoting tissue repair. Issue 12 (17th August 2021) - Joo, Gyeongjin; Sultana, Tamanna; Rahaman, Sohanur; Bae, Sang Ho; Jung, Hae Il; Lee, Byong-Taek
Abstract: Anastomotic leakage due to post-surgical suture line disruption is one of the crucial factors affecting patient's survival and quality of life. To resolve the poor healing of surgical anastomosis and protect suture sites leakage, fibrous membrane sealing patch was developed using a synthetic polymer (polycaprolactone (PCL)) and biopolymer (gelatin). Electrospinning was used to develop fibrous architecture of membranes fabricated in different ratios (15% (w/v) PCL: 15% (w/v) gelatin mixing ratio of 1:1, 1:2, 1:3 and 1:4). Experimental findings suggested that, higher gelatin content in the membranes reduced the fiber diameter and contact angle, leading to a more hydrophilic scaffold facilitating attachment to the defect site. The degradation rate of various PCL-gelatin membranes (P1G1, P1G2, P1G3 and P1G4) was proportional to the gelatin content. Cytocompatibility was assessed using L929 cells while the P1G4 (PCL: gelatin 1:4 ratio) scaffold exhibited optimum outcome. From in vivo study, the wound site healed significantly without any leakage when the sutured area of rat caecum was covered with P1G4 membrane whereas rats in the control group (suture only) showed leakage after two weeks of surgery. In summary, the P1G4 membrane has potential to be applied as a post-surgical leakage-preventing tissue repair biomaterial.